The Impact of Foreign Direct Investment on Dubai's Real Estate Market (2000–2025) - De Vries, Jakub (2025)
This thesis examines the impact of foreign direct investment (FDI), market fundamentals, and significant policy reforms on real estate prices in Dubai from 2000 to 2025. Using annual data from the Dubai Land Department, the Central Bank of the UAE, and international sources, the analysis applies ARIMA-based stationarity adjustments and several OLS model specifications. The results show that FDI alone does not significantly affect prices, but becomes more relevant when combined with variables such as supply, transaction activity, and interest rates. Interest rates consistently emerge as a key determinant, reflecting Dubai’s dependence on global monetary conditions. Among policy interventions, the Golden Visa has no measurable price effect, while the 2020 foreign ownership reform shows a significant positive impact. The best-performing model is the post-2010 specification, indicating a more stable and mature market in recent years. Real estate prices are primarily shaped by macroeconomic conditions and structural reforms, rather than short-term foreign inflows.